Production and postharvest management for Dendrobium orchids - Biswas, Siddhartha Sankar; Pal, Ram; S, Kalaivanan N; M, Ngangom N; Natta, Suman (Indian Horticulture, 2023)
The Dendrobium genus of orchids mostly comprises of epiphytic and lithophytic type of orchids. This large genus contains 1,800 species which are distributed in diverse habitats of south, east and south-east Asia, including India, China, Japan, Indonesia, Philippines, Australia, Vietnam, New Guinea and many parts of the Pacific islands. It has immense importance as commercial floricultural crop for subtropical India. Roots of these orchids generally creep over the bark of trees (for epiphytes) or rocks (for lithophytes). They rarely insert their roots in soil. As the crop has mostly epiphytic or lithophytic growth habit, it requires some special conditions and nourishment. It can not be grown in pots having soil as potting media. To mimic epiphytic conditions, special potting media, nutritional management, special growing condition, disease and pest management are required. These complete management practices largely differ from agricultural or horticultural crops. In this article, the cultivation requirements of Dendrobium orchids have been elaborated.